Study habits: crucial factor for good academic environment (Revista Innova Educación, 2020)
It is important that university students recognize different methods and study techniques; and moreover, analyze and incorporate them into their habits. Currently, one of the limitations for the future academic development, is the lack of knowledge of learning and understanding modalities, whose impact affects the academic performance. The objective of the study was to determine the level of association between study habits and academic performance of students from the second and third cycle of the Faculty of Nursing at the National University of the Altiplano in Puno, Peru. The sample of the study was based on 77 students, selected under inclusion and exclusion criteria. The research has a non-experimental, transversal and correlational approach. The study technique was the survey with its instruments of qualitative note taking and the Inventory of Study Habits, whose validity and reliability has a value of 0.82 through the equation K-R 20. The results show that study habits are associated with a good level of academic performance, proven by 66.2% of students; on the other hand, the use of inadequate study habits are predominantly associated with an average academic performance represented by 9.1% of students. Also, 74% of students have good academic performance, 83.1% have adequate study habits and 45.5% have a negative trend during test preparation. The hypothesis test concludes that, there is a statistically significant association between study habits and academic performance in nursing students with the value of p-0.009 < p-0.05.
Keywords: Habits; students; academic performance